Secure and efficient data storage and sharing scheme for blockchain‐based mobile‐edge computing. Issue 10 (6th June 2021) - Zhang, Lejun; Peng, Minghui; Wang, Weizheng; Jin, Zilong; Su, Yansen; Chen, Huiling
Abstract: With the rapid development of Internet of Things (IoT) technology, IoT devices have been widely used to collect physiological health data and provide diversified services to the terminal users. However, traditional data storage and sharing scheme cloud computing based in IoT face many challenges. For example, IoT devices are usually resource‐constrained (storage, computing power, battery capacity, etc.), data signed by IoT devices to ensure data integrity and authenticity will consume a lot of computing resources of IoT devices. At the same time, there is the challenge of high latency and unsafe data storage and sharing. To overcome these challenges, we propose a secure and efficient data storage and sharing scheme for blockchain‐based mobile‐edge computing. In our scheme, we construct the unique signature private key in a region into multiple key shares. IoT devices only need to submit the data and the random key shares allocated to the edge node. Edge node uses the recovered signature private key to realize data signature and homomorphic encryption. At the same time, the edge node will process timely data and return to the user. For data that need to be uploaded to the cloud for analysis, we use backup uploads to avoid data floods. Through experiments, it was found that our scheme can not only realize low‐latency message response for the terminal users, but also realize anonymous identity verification while ensuring data integrity and authenticity. The key shares of the signature private key are stored in different blocks of the blockchain to improve fault tolerance. The content extraction signature algorithm ensures that the key shares stored in different blocks are publicly verifiable. Safety analysis and performance analysis verify the feasibility and effectiveness of our scheme. Abstract : IoT devices submit data and share of keys. Trusted proxy nodes implement data signatures and homomorphic encryption to ensure data integrity and protect privacy, at the same time, this scheme reduces the burden of resource‐constrained IoT devices. Blockchain is used to store data index and key share to achieve tamper resistance and enhance fault tolerance.